The Health Informatics Centre: a Regional Safe Haven and Trusted Research Environment Enabling World-Leading Research - Ward, Laura; Johnston, Jenny; Milburn, Keith; Hall, Christopher; Jones, Claire; Guignard-Duff, Magalie; Krueger, Susan; Milligan, Gordon; Anderson, Jill; Walls, Richard; Cole, Christian (International Journal of Population Data Science, 2026)
Introduction The Health Informatics Centre (HIC) is a regional Scottish Safe Haven dedicated to secure data management, ensuring its integrity, confidentiality, and availability through a robust information governance framework. Methods As a data processor, HIC is responsible for the secure curation, storage, and provision of research data extracts. Research-ready data are made available to approved researchers via our customisable cloud Trusted Research Environment (TRE). Results The available granular data spans over 20 years, includes 2.1 million of the Scottish population, and HIC offers more than 170 datasets, with the most commonly used published with a digital object identifier. Data sources include clinical, hospital, laboratory, imaging, and research datasets which can be linked to new, and existing datasets. The data is quality-assured and released as project-specific extracts, ensuring robust privacy protection and research readiness. HIC's infrastructure is secure-by-design and supports high-performance computing, advanced data analytics, and is customisable to researcher's needs. Conclusion HIC has a long history of supporting a wide range of data-led research projects as a trusted and capable partner. At the time of publication 175 projects across academia, the NHS, and public sector organisations are active within HIC. Through adaptability, innovation and investment in people and infrastructure we have established a sustainable model which will continue to meet future needs and demands from world-leading research with sensitive data.